ATG7-deficient fibroblast promotes breast cancer progression via exosome-mediated downregulation of SCARB1 - Kangdi Li; Ting Liu; Zhihong Luo; You Yu; Yi Liu; Zhaoqing Zhang; Wenhua Li (Cell Death and Disease)
Abstract Although autophagy-related gene 7 (ATG7) acts as an E1-like activating enzyme and is essential for autophagy, it frequently performs broader roles involved in the modulation of diverse signaling pathways that affect cell proliferation, survival, migration and transformation. ATG7 is often downregulated in various cancers. However, the role of ATG7 in fibroblasts in regulating breast carcinoma remains poorly understood. Herein, we revealed that aberrantly low expression of ATG7 in breast stroma is clinically relevant to breast cancer progression. Loss of ATG7 expression results in fibroblasts acquiring the hallmarks of cancer-associated fibroblasts (CAFs), which finally promote the proliferation, metastasis of breast cancer in vivo and vitro. Detailed regulatory mechanisms showed that ATG7-deficient fibroblasts secrete a new miRNA (miR-6803b) and are then transported into breast cancer cells by exosomes. In breast cancer, miR-6803b targets the SCARB1 gene to inhibit its expression and then promote cancer cell metastasis, resulting in cancer progression. Thus, our results indicate that ATG7 expression in fibroblasts plays a vital role in regulating breast cancer tumorigenesis and progression by modifying stromal–epithelial crosstalk and remodeling the tumor microenvironment (TME). These results suggest that ATG7 can function as a tumor suppressor and represent a new candidate for prognosis and targeted therapy.